2016
DOI: 10.1016/j.biortech.2015.10.062
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal carbonization of industrial mixed sludge from a pulp and paper mill

Abstract: Please cite this article as: Mäkelä, M., Benavente, V., Fullana, A., Hydrothermal carbonization of industrial mixed sludge from a pulp and paper mill, Bioresource Technology (2015), doi: http://dx.doi.org/10.1016/j.biortech. 2015.10.062 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…As a result of these reactions, value-added solid, liquid and gas products are generated. The properties of these products largely depend on the starting feedstock and operating conditions (e.g., Falco et al, 2011;Girotto et al, 2015;Hoekman et al, 2013;Li et al, 2015;Lu et al, 2013;Lu, 2014;Mäkelä et al, 2016;Nizamuddin et al, 2016). Several recent reviews have detailed different aspects of carbonization, including reaction mechanisms (Funke and Ziegler, 2010b;Kruse et al, 2013;Libra et al, 2011), effect of process parameters (Hoekman et al, 2011;Nizamuddin et al, 2017), recovery of valuable liquid and solid products (Reza et al, 2014), and material synthesis for various material and/or environmental applications (Libra et al, 2011;Titirici et al, 2012).…”
Section: Thesis Organizationmentioning
confidence: 99%
“…As a result of these reactions, value-added solid, liquid and gas products are generated. The properties of these products largely depend on the starting feedstock and operating conditions (e.g., Falco et al, 2011;Girotto et al, 2015;Hoekman et al, 2013;Li et al, 2015;Lu et al, 2013;Lu, 2014;Mäkelä et al, 2016;Nizamuddin et al, 2016). Several recent reviews have detailed different aspects of carbonization, including reaction mechanisms (Funke and Ziegler, 2010b;Kruse et al, 2013;Libra et al, 2011), effect of process parameters (Hoekman et al, 2011;Nizamuddin et al, 2017), recovery of valuable liquid and solid products (Reza et al, 2014), and material synthesis for various material and/or environmental applications (Libra et al, 2011;Titirici et al, 2012).…”
Section: Thesis Organizationmentioning
confidence: 99%
“…Figure S1, supplied as supplementary material and taken from reference [25] shows the strong interaction of variables during HTC of tomato waste. Makela et al [28] used response-surface contour plots to show the effect of HCl or NaOH on the HTC of sludge from a pulp and paper mill. The result show that the pattern solid yield as a function of temperature and time is not affected by the addition of acid or base.…”
Section: Statistical Modelsmentioning
confidence: 99%
“…It should be noted that the wavelength accuracy of hyperspectral cameras is generally not as high as that of spectrometers, and the literature on wavelength assignments within the NIR region still remains very incomplete. Previous results on mixed sludge chars have shown that hydrothermal treatment did not lead to significant changes in solid‐state NMR spectra until a temperature of 260 °C was used . Based on the data, aliphatic carbon signals largely disappeared at higher temperatures, but the shifts for acetyl methyl groups of cellulose suggested that some alkyl carbon was still present in the chars.…”
Section: Discussionmentioning
confidence: 87%